1997
DOI: 10.1143/jjap.36.l8
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Diamond Nucleation Processes on Carbonized Substrates

Abstract: The formation of carbonized interface layers is a spontaneous stage in the nucleation process of the chemical vapor deposition (CVD) of diamond onto substrates, however, the relationship between the carbonization and nucleation stages has not been well understood to date. This paper will discuss diamond nucleation mechanisms in relation to the carbonization of silicon substrates. For this purpose the silicon substrates are first carbonized using direct resistive heating. Then, diamonds are deposited on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…10 Real-time ellipsometry is a powerful method for the precise and accurate analysis of thin film structures and growth processes, and already has been applied to the processes of diamond film syntheses without BEN. [11][12][13][14][15] It has been shown that single-wavelength ellipsometry has a fast response and sensitive measurements in the early stages of diamond film growth: 11,12,14,15 the time evolution of film thickness has been evaluated and diamond nucleation processes have been analyzed. BEN has already been applied to a hot-filament chemical vapor deposition ͑HF-CVD͒ by other research groups; 16,17 however the effect of bias application in the HF-CVD of diamond has not been clarified.…”
Section: Department Of Electronics and Information Science Kyoto Insmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Real-time ellipsometry is a powerful method for the precise and accurate analysis of thin film structures and growth processes, and already has been applied to the processes of diamond film syntheses without BEN. [11][12][13][14][15] It has been shown that single-wavelength ellipsometry has a fast response and sensitive measurements in the early stages of diamond film growth: 11,12,14,15 the time evolution of film thickness has been evaluated and diamond nucleation processes have been analyzed. BEN has already been applied to a hot-filament chemical vapor deposition ͑HF-CVD͒ by other research groups; 16,17 however the effect of bias application in the HF-CVD of diamond has not been clarified.…”
Section: Department Of Electronics and Information Science Kyoto Insmentioning
confidence: 99%
“…19 Through diffusion, microindentions, i.e., voids, are created at the top of a silicon substrate. 15 Then the optically equivalent thickness for the first 2 min is due to a surface layer mainly including weakly bonded carbon like sp 2 one, sp 3 carbon, silicon, voids, and Si-C. The abrupt interruption of the thickness increase arises from the etching of the surface layer, especially weakly bonded carbon, by ions: the ion energy exceeds the threshold energy for sputter etching, which is generally several tens of eV.…”
Section: Department Of Electronics and Information Science Kyoto Insmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such abrasion methods damage the surface in a poorly defined manner. Thus, more controlled methods of nucleation such as biasing prior to CVD are becoming increasingly common [11,12] and can even enable heteroepitaxial growth of diamond films [13,14]. The gas-phase environment during deposition also affects the quality and morphology of the resulting diamond films.…”
Section: Introductionmentioning
confidence: 99%